Metabolic phenotype of skeletal muscle in early critical illness. Issue 10 (6th July 2018) - Puthucheary, Zudin A; Astin, Ronan; Mcphail, Mark J W; Saeed, Saima; Pasha, Yasmin; Bear, Danielle E; Constantin, Despina; Velloso, Cristiana; Manning, Sean; Calvert, Lori; Singer, Mervyn; Batterham, Rachel L; et al.
Abstract : Objectives: To characterise the sketetal muscle metabolic phenotype during early critical illness. Methods: Vastus lateralis muscle biopsies and serum samples (days 1 and 7) were obtained from 63 intensive care patients (59% male, 54.7±18.0 years, Acute Physiology and Chronic Health Evaluation II score 23.5±6.5). Measurements and main results: From day 1 to 7, there was a reduction in mitochondrial beta-oxidation enzyme concentrations, mitochondrial biogenesis markers (PGC1α messenger mRNA expression (−27.4CN (95% CI −123.9 to 14.3); n=23; p=0.025) and mitochondrial DNA copy number (−1859CN (IQR −5557–1325); n=35; p=0.032). Intramuscular ATP content was reduced compared tocompared with controls on day 1 (17.7mmol/kg /dry weight (dw) (95% CI 15.3 to 20.0) vs. 21.7 mmol/kg /dw (95% CI 20.4 to 22.9); p<0.001) and decreased over 7 days (−4.8 mmol/kg dw (IQR −8.0–1.2); n=33; p=0.001). In addition, the ratio of phosphorylated:total AMP-K (the bioenergetic sensor) increased (0.52 (IQR −0.09–2.6); n=31; p<0.001). There was an increase in intramuscular phosphocholine (847.2AU (IQR 232.5–1672); n=15; p=0.022), intramuscular tumour necrosis factor receptor 1 (0.66 µg (IQR −0.44–3.33); n=29; p=0.041) and IL-10 (13.6 ng (IQR 3.4–39.0); n=29; p=0.004). Serum adiponectin (10.3 µg (95% CI 6.8 to 13.7); p<0.001) and ghrelin (16.0 ng/mL (IQR −7–100); p=0.028) increased. Network analysis revealed a close and direct relationship between bioenergetic impairment and reduction in muscle mass and between intramuscular inflammation and impaired anabolic signaling. ATP content and muscle mass were unrelated to lipids delivered. Conclusions: Decreased mitochondrial biogenesis and dysregulated lipid oxidation contribute to compromised skeletal muscle bioenergetic status. In addition, intramuscular inflammation was associated with impaired anabolic recovery with lipid delivery observed as bioenergetically inert. Future clinical work will focus on these key areas to ameliorate acute skeletal muscle wasting. Trial registration number: NCT01106300 .